2018
DOI: 10.1021/acs.molpharmaceut.8b00129
|View full text |Cite
|
Sign up to set email alerts
|

Improved Predictions of Drug–Drug Interactions Mediated by Time-Dependent Inhibition of CYP3A

Abstract: Time-dependent inactivation (TDI) of cytochrome P450s (CYPs) is a leading cause of clinical drug–drug interactions (DDIs). Current methods tend to overpredict DDIs. In this study, a numerical approach was used to model complex CYP3A TDI in human-liver microsomes. The inhibitors evaluated included troleandomycin (TAO), erythromycin (ERY), verapamil (VER), and diltiazem (DTZ) along with the primary metabolites N-demethyl erythromycin (NDE), norverapamil (NV), and N-desmethyl diltiazem (NDD). The complexities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 117 publications
0
42
0
Order By: Relevance
“…Victim Drug Therapeutic drug class F g (Galetin et al, 2008) f m (Shou et al, 2008) AUCR (Mano et al, 2015) b (Yadav et al, 2018) c (Mao et al, 2011) f m , fraction of the object drug cleared by CYP3A; F g , fraction of the object drug escaping CYP3A-mediated metabolism in the gut; AUCR, ratio of area under the plasma concentrationtime curve in presence to absence of inhibitor This article has not been copyedited and formatted. The final version may differ from this version.…”
Section: Figure Legendsmentioning
confidence: 99%
“…Victim Drug Therapeutic drug class F g (Galetin et al, 2008) f m (Shou et al, 2008) AUCR (Mano et al, 2015) b (Yadav et al, 2018) c (Mao et al, 2011) f m , fraction of the object drug cleared by CYP3A; F g , fraction of the object drug escaping CYP3A-mediated metabolism in the gut; AUCR, ratio of area under the plasma concentrationtime curve in presence to absence of inhibitor This article has not been copyedited and formatted. The final version may differ from this version.…”
Section: Figure Legendsmentioning
confidence: 99%
“…Atypical kinetics (i.e., non-Michaelis-Menten) are widely observed with P450s (Korzekwa et al, 1998;Atkins, 2005;Korzekwa, 2014;Leow and Chan, 2019), which have mechanistically been attributed to multiple binding (Korzekwa et al, 1998), protein heterogeneity (Davydov and Halpert, 2008), enzyme oligomerization, protein-protein interactions (Davydov et al, 2017;Davydova et al, 2019), or a combination. Atypical kinetics can profoundly impact TDI kinetics (Korzekwa et al, 2014;Nagar et al, 2014), and evidence suggests DDI predictions can be improved by accounting for mechanistic complexities (Yadav et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The concave upward curvature is indicative of either quasi-irreversible or partial inactivation as shown previously (Nagar et al, 2014) Using the numerical method (Korzekwa et al, 2014;Nagar et al, 2014), kinetic models were fit to the data, and kinetic parameters were estimated. The initial estimates of the rate constants were obtained from analyzing the data as detailed in previous publications (Korzekwa et al, 2014;Nagar et al, 2014;Barnaba et al, 2016;Yadav et al, 2018;Yadav et al, 2020). Association rate constants were fixed at 270 μM -1 min −1 (Barnaba et al, 2016).…”
Section: Model Fitting Using the Numerical Methods And Estimate Of Tdimentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown previously that using numerical methods to model TDI data has several advantages over the traditional replot method (Korzekwa et al, 2014;Nagar et al, 2014;Yadav et al, 2018): 1) Michaelis-Menten kinetics (MM) is not assumed and the frequently observed non-MM kinetics can be easily modeled; 2) parameter errors in all models (including MM) are significantly lower due to the lack of propagation of errors seen in the replot method; 3) other complexities such as quasi-irreversible inactivation, inhibitor loss, and sequential (Seq) metabolism can be modeled; and 4) the use of the numerical method has been shown to result in more accurate DDI predictions than the replot method. The replot method does have two advantages when MM kinetics applies.…”
Section: Introductionmentioning
confidence: 99%